Sex differences in the effects of chronic stress and food restriction on body weight gain and brain expression of CRF and relaxin‐3 in rats. (12th March 2013) - Lenglos, C.; Mitra, A.; Guèvremont, G.; Timofeeva, E.
<x xml:space="preserve">Abstract</x> This study investigated sex‐specific effects of repeated stress and food restriction on food intake, body weight, corticosterone plasma levels and expression of corticotropin‐releasing factor (CRF) in the hypothalamus and relaxin‐3 in the nucleus incertus (NI). The CRF and relaxin‐3 expression is affected by stress, and these neuropeptides produce opposite effects on feeding (anorexigenic and orexigenic, respectively), but sex‐specific regulation of CRF and relaxin‐3 by chronic stress is not fully understood. Male and female rats were fed ad libitum chow (AC) or ad libitum chow and intermittent palatable liquid Ensure without food restriction (ACE), or combined with repeated food restriction (60% chow, 2 days per week; RCE). Half of the rats were submitted to 1‐h restraint stress once a week. In total, seven weekly cycles were applied. The body weight of the RCE stressed male rats significantly decreased, whereas the body weight of the RCE stressed female rats significantly increased compared with the respective control groups. The stressed female RCE rats considerably overate chow during recovery from stress and food restriction. The RCE female rats showed elevated plasma corticosterone levels and low expression of CRF mRNA in the paraventricular hypothalamic nucleus but not in the medial preoptic area. The NI expression of relaxin‐3 mRNA was significantly higher in the stressed RCE female rats compared with other groups. An increase in the expression of orexigenic relaxin‐3 and misbalanced hypothalamic‐pituitary‐adrenal axis activity may contribute to the overeating and increased body weight seen in chronically stressed and repeatedly food‐restricted female rats.